2013
DOI: 10.1016/j.ceca.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Purine receptor mediated actin cytoskeleton remodeling of human fibroblasts

Abstract: Earlier studies have shown that activation of adenosine A1 receptors on peripheral pain fibers contributes to acupuncture-induced suppression of painful input. In addition to adenosine, acupuncture triggers the release of other purines, including ATP and ADP that may bind to purine receptors on nearby fibroblasts. We here show that purine agonists trigger increase in cytosolic Ca 2+ signaling in a cultured human fibroblasts cell line. The profile of agonist-induced Ca2+ increases indicates that the cells expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
2
32
0
2
Order By: Relevance
“…Scar tissue and fibrotic tissue are typically painful, structurally thicker and less elastic than healthy tissue [112]. However, DN mediated mechanotransduction of fibroblasts may be able to help remodel painful tissue by dampening tissue tension via actin polymerization [110]. A number of studies have demonstrated the use of DN to reduce pain associated with scar [58,113] and fibrotic tissue [114] further supporting this possibility.…”
Section: Dry Needling Mechanotransduction and Tissue Restructuringmentioning
confidence: 77%
See 3 more Smart Citations
“…Scar tissue and fibrotic tissue are typically painful, structurally thicker and less elastic than healthy tissue [112]. However, DN mediated mechanotransduction of fibroblasts may be able to help remodel painful tissue by dampening tissue tension via actin polymerization [110]. A number of studies have demonstrated the use of DN to reduce pain associated with scar [58,113] and fibrotic tissue [114] further supporting this possibility.…”
Section: Dry Needling Mechanotransduction and Tissue Restructuringmentioning
confidence: 77%
“…Simply put, a reduction of fibroblast stress fibers changes the viscoelastic properties of the cells, allowing them to be more easily remodeled. Interestingly, this process requires mechanotransduction, as using cyclopiazonic acid to increase intracellular Ca 2+ was not enough to alter the actin cytoskeleton in the absence of P2X/P2Y receptor activation [110]. Moreover, the inhibition of rho kinase, a product of DN-mediated mechanotransduction, prevented viscoelastic changes in fibroblasts [110,111].…”
Section: Dry Needling Mechanotransduction and Tissue Restructuringmentioning
confidence: 99%
See 2 more Smart Citations
“…19 A role of purines (ATP, ADP, adenosine) in the periphery is supported by Goldman and collaborators who have shown that activation of adenosine A1 receptors on peripheral pain fibres contributes to acupunctureinduced suppression of painful input. [20][21][22] An obvious question is whether needling of skin or muscles makes a difference to the perception of de qi. Skin pain is a sharp, spatially localised sensation, whereas muscle pain is a dull and poorly localised one.…”
Section: Needling Sensation and Analgesiamentioning
confidence: 99%